(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Entrepreneurship, defined in this study as the development of new enterprises focusing on social and community outcomes and financial objectives, is increasingly becoming a focus of empirical research. Entrepreneurs whose distinct and specific motivations have yet to be extensively studied represent an essential component of such new business development. Social entrepreneurship is an approach by individuals, groups, start-ups, or entrepreneurs in which they develop, fund, and implement solutions to social, cultural, or environmental issues. This concept may be applied to various organizations, which vary in size, aims, and beliefs. For-profit entrepreneurs typically measure performance using business metrics like profit, revenues, and increases in stock prices. The researchers used a quantitative-descriptive research design. This study aims to know the factors affecting the choice of BS Entrepreneur Course among ABM students at Bestlink College of the Philippines. Fifty respondents from sections 1-10 were selected through simple random sampling. Based on the findings of the study, the reason why there are a lot of students who don’t consider this course even though it’s a good choice is that it started in 1983 at DLSU, which is known as one of the prestigious schools here in the Philippines that’s only for rich people/family meaning it doesn’t have an exposure’s on the public, especially in non-private schools. The Philippines is also known as one of the poorest countries in the world, which is why, in the early 1980s, most the people who were not financially stable put risk and started a business so when they had a chance to go to college, they chose the course that has a good income or has a lot of work opportunity so that they can work right after they finished college to provide not just for themselves, future rather but also for their family’s needs. This also proves that what we put on our SOP is true: family, friends, society, financial stability, and so on are the factors that affect the students in choosing BS Entrepreneurship. School Organizations the government rather should expand BS Entrepreneurship in the whole part of the Philippines. Government/Schools should organize a plan to expand it, especially in Public Schools/Communities, so that students who want to take this course will have a chance to fulfil their dream without spending a lot of money by getting a scholarship from the government, for adults to be aware that there’s an existing course for their children who wants to take Entrepreneurship course or to be aware that this course exists if their children want to convince them. It can be done by conducting a seminar in every barangay so people can acknowledge it on social media platforms since every teenager is on social media, television or radio. Making a program or team building with the students and parents, especially in the secluded area about Entrepreneurship is known for being innovative, which helps a nation to improve what we already have so that business will rise as well as the economic rate and the country itself. In our current generation, there are a lot of successful entrepreneurs, even the younger generation, who are innovative in their products, so expanding the BS Entrepreneurship course will encourage more students to take or consider BS Entrepreneurship, which can bring success to them and the country.